Prevention Effortsonline Gambling Crimes Among Students of the State Islamic University of North Sumatra According to the Views of Law Lecturers of the Faculty of Sharia and Law - Nazwa Sabrina Naslim; Madya Dr. Jasni bin Sulong (Program Pascasarjana UIN Sumatera Utara Medan, 2019)
This study aims to analyze efforts to prevent the increasingly widespread crime of online gambling among students based on the perspectives of law lecturers at the Faculty of Sharia and Law. The rapid development of digital technology and internet accessibility has contributed to the rising prevalence of online gambling activities, particularly among young people and university students. This phenomenon poses serious concerns due to its negative consequences on academic performance, financial stability, mental health, and social behavior. The study highlights various adverse impacts of online gambling, including cheating, exploitation, fraud, addiction, and involvement in criminal activities. Furthermore, it examines the factors influencing the effectiveness of prevention and eradication efforts, encompassing legal regulations, law enforcement mechanisms, socio-cultural conditions, community participation, educational awareness, and supporting infrastructure. This research employs a qualitative approach by exploring the views and legal perspectives of lecturers specializing in law and Islamic legal studies. The findings reveal that strengthening legal awareness, improving law enforcement, enhancing digital literacy, and promoting preventive education among students are essential strategies in combating online gambling practices. The implementation of positive law and criminal law enforcement is considered crucial in creating deterrent effects and protecting students from the harmful influence of online gambling. In addition, collaboration between educational institutions, families, government agencies, and society is necessary to develop comprehensive prevention measures. This study is expected to contribute as a reference for policymakers and educational institutions, particularly within the State Islamic University of North Sumatra, in formulating effective policies and strategies to prevent online gambling crimes among students and foster a safer academic environment.